Pengaruh Strategi Bauran Pemasaran terhadap Penjualan Produk Sembako pada CV. Cahaya Benteng di Makassar - Muhtazib Muhtazib; Andi bintang Balele (BADAN PENERBIT STIEPARI PRESS, 2022)
The aim of the research is to determine the influence of the marketing mix on sales of basic food products and to determine the dominant variables that influence sales of basic food products at CV. The Light of the Fortress in Makassar, South Sulawesi Province. The research methods used are qualitative and quantitative research methods. The results of the research are that from the F test (simultaneous test) it turns out that independent factors have a significant influence on increasing sales of basic necessities in Makassar. And furthermore, it is known that the calculated F value is greater than table F, this means that product, price, distribution and promotion factors together have a significant influence on basic food sales at CV. Light of the Fortress in Makassar. According to the results of the Multiple Regression calculation, the coefficient of determination (R2) shows that all independent factors together have a fairly strong influence on the dependent variable (grocery sales). From the results of the Partial Test (T Test) it can be seen that the most significant factor influences the sales of basic necessities at CV. The Light of the Fort in Makassar is a Promotional factor.